Skeletal nutrient vascular adaptation induced by external oscillatory intramedullary fluid pressure intervention - Qin Yi-Xian; Brink Peter; Lam Hoyan (Journal of Orthopaedic Surgery and Research, 2010)
Abstract Background Interstitial fluid flow induced by loading has demonstrated to be an important mediator for regulating bone mass and morphology. It is shown that the fluid movement generated by the intramedullary pressure (ImP) provides a source for pressure gradient in bone. Such dynamic ImP may alter the blood flow within nutrient vessel adjacent to bone and directly connected to the marrow cavity, further initiating nutrient vessel adaptation. It is hypothesized that oscillatory ImP can mediate the blood flow in the skeletal nutrient vessels and trigger vasculature remodeling. The objective of this study was then to evaluate the vasculature remodeling induced by dynamic ImP stimulation as a function of ImP frequency. Methods Using an avian model, dynamics physiological fluid ImP (70 mmHg, peak-peak) was applied in the marrow cavity of the left ulna at either 3 Hz or 30 Hz, 10 minutes/day, 5 days/week for 3 or 4 weeks. The histomorphometric measurements of the principal nutrient arteries were done to quantify the arterial wall area, lumen area, wall thickness, and smooth muscle cell layer numbers for comparison. Results The preliminary results indicated that the acute cyclic ImP stimuli can significantly enlarge the nutrient arterial wall area up to 50%, wall thickness up to 20%, and smooth muscle cell layer numbers up to 37%. In addition, 3-week of acute stimulation was sufficient to alter the arterial structural properties, i.e., increase of arterial wall area, whereas 4-week of loading showed only minimal changes regardless of the loading frequency. Conclusions These data indicate a potential mechanism in the interrelationship between vasculature adaptation and applied ImP alteration. Acute ImP could possibly initiate the remodeling in the bone nutrient vasculature, which may ultimately alter blood supply to bone.